An analysis of the availability of health education materials to improve children's healthy behaviours in the school environment - Tuti Rohani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Backgound: Health education is the provision of health knowledge and habituation of healthy behaviour of students. The adequacy of health education provision will affect the attitudes and behaviour of school children which will determine their health status whether they will remain healthy or at risk of health problems in the present and adulthood. Purpose: To analyze the availability of health education materials to improve children's healthy behaviours in the school environment. Method: This descriptive qualitative research analyses by examining and revealing the meaning or reality of Health Education conducted in Primary Schools. This research was conducted in five primary schools in the Bengkulu city area, with data analysis techniques including data reduction steps, presenting data, drawing conclusions for verification. Data validity checks with source triangulation through activities to test the credibility of data triangulation techniques for data credibility by checking data to the same source with different techniques. Interview results are checked with documentation or observation. Results: The results of the research on the school health center program have not been able to run optimally as seen from the policies and guidelines that do not yet exist and are well socialised to all school members. The school health center supervisor teacher, teacher of physical education sports and health and guardian teacher have not fully implemented the Trias school health center and understood the indicators in school health center activities. The school health center is still the responsibility of the community health centre. Students have never received health education intensively. Health education in schools has a significant influence on students' health behaviour. Conclusion: Through purposeful health education, students can increase their knowledge about health. Health education also plays an important role in changing behaviour, resulting in the adoption of healthy behaviours in students. Students who receive effective health education tend to adopt healthy behaviours.